A relação entre os ciclos econômicos e a distribuição funcional da renda nas grandes regiões do Brasil : 2004-2018 - Solano, Fernanda Picoral (2022)
This dissertation employs the Goodwin model to explain the relationship between economic cycles and the functional income distribution for five Brazilian regions between 2004 and 2018. The Goodwin cycle shows a non-linear relationship between the level of employment and the wage share. The methodology employed consisted of two stages. The first was the collection and organization of data set. The second was the investigation for the presence of the Goodwin cycles in the Brazilian regions. The results were consistent with the presence of the Goodwin cycle in the period under study for Brazil and for the five major regions. The years 2009 and 2014 were moments of change in the cyclical movement for all regions, which indicated that more accentuated crises change the direction of movement in the expected way by the model and that national factors have decisive effects on regional cycles.